(untitled) (SIRJANĀ – A Journal Of Arts and Art Education, 2024)
History of the Nepali music is very hoary. Nonetheless, apart from a few of the collections of old and new songs, books written on the Nepali music are very rare. In this context, the books written by native and foreign authors are obviously highly valued. In addition, books authored by the one who has been long associated with the field of Nepali music would be essentially substantial. The book reviewed here falls in the same category. Prof. Dr. Dhrubesh Chandra Regmi, a renowned music scholar and performer is an exponent of sitar belonging to the illustrious Regmi gharana (the musical family) of Nepal. He has been involved in the field of higher education of music since quite a long time as well as. In this sense, the book authored by him is very important from different perspectives.